1,2,3-TRIAZOLIUM SALTS DERIVATIVES AS ANTICANCER REAGENTS (World Bulletin of Public Health, 2023)
A group of organic compounds known as 1,2,3-triazolium salts include the triazolium cation, a five-membered ring made up of three nitrogen and two carbon atoms. Due to their wide spectrum of characteristics and prospective uses in chemistry, materials science, and medicine, these compounds have attracted a lot of attention in recent years. The triazolium ring's substituents can be changed to create derivatives of 1,2,3-triazolium salts. The type and location of these substituents have a significant impact on the compound's characteristics and reactivity. Some 1,2,3-triazolium salt compounds have demonstrated strong biological activity, including antibacterial, antifungal, and anticancer activities. This makes them potential candidates for the development of new drugs and therapies. 1,2,3-Triazolium salts derivatives have shown potential as anticancer reagents due to their ability to selectively target cancer cells and inhibit their growth. These derivatives exhibit cytotoxicity towards cancer cells while demonstrating minimal toxicity towards normal healthy cells. This review provides a comprehensive overview of synthetic strategies for the preparation of 1,2,3-triazolium salts and highlights the structures of various derivatives that exhibit biological activities (anti-cancer). It is important to note that the development of 1,2,3-triazolium salts derivatives as anticancer reagents is an active area of research, and specific compounds and mechanisms may vary. Further studies are required to optimize their efficacy, selectivity, and safety profiles before their clinical application
Keywords: Synthesis; 1,2,3-Triazolium Salts; Triazole Ring; Anticancer